2021
DOI: 10.1089/ars.2020.8169
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-to-Mesenchymal Transition in Pulmonary Arterial Hypertension

Abstract: Endothelial-to-mesenchymal transition (EndMT) is a process that encompasses extensive transcriptional reprogramming of activated endothelial cells leading to a shift toward mesenchymal cellular phenotypes and functional responses. Initially observed in the context of embryonic development, in the last few decades EndMT is increasingly recognized as a process that contributes to a variety of pathologies in the adult organism. Within the settings of cardiovascular biology, EndMT plays a role in various diseases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 216 publications
(302 reference statements)
1
63
0
Order By: Relevance
“…The increase in calpain-1/2 associated with Piezo1-driven Ca 2 þ influx may also contribute to the development of pulmonary vascular remodeling by inducing extracellular matrix remodeling, vascular fibrosis, and arterial calcification (47,49,50,88). Calpain may also activate TGF-b1 and AKT/mTORC2 signaling (50) and induce EndMT in PAECs (89)(90)(91).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in calpain-1/2 associated with Piezo1-driven Ca 2 þ influx may also contribute to the development of pulmonary vascular remodeling by inducing extracellular matrix remodeling, vascular fibrosis, and arterial calcification (47,49,50,88). Calpain may also activate TGF-b1 and AKT/mTORC2 signaling (50) and induce EndMT in PAECs (89)(90)(91).…”
Section: Discussionmentioning
confidence: 99%
“…The Jag-mediated Notch activation in PASMCs can also result in small arterial wall thickening and arteriole muscularization by stimulating PASMC proliferation and recruitment (61,82,125). The ECs with upregulated Jag-1/2/3 can also interact with adjacent ECs to induce EndMT by activating endothelial Notch receptors (126-128) and, potentially, cause occlusive intimal lesions (83,89,91,122,129,130). Stretch-mediated opening of upregulated Piezo1 channels in PAECs may lead to Ca 2 þ -dependent SNAI1 expression (131) causing EndMT and to Ca 2 þ -dependent growth factor (e.g., PDGF) synthesis (132,133) causing arteriole muscularization via a paracrine mechanism (134)(135)(136).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that EndMT potentially contributes to endothelial dysfunction and the vascular remodeling of PAH [ 7 , 11 , 22 , 23 ]. Indeed, many studies have demonstrated that various signaling pathways and mediators, including transforming growth factor beta (TGFβ), nuclear factor kappa B (NF-κB), Notch, and microRNA, are involved in the EndMT of PAH [ 24 , 25 ]. It has been reported that the endothelial-specific loss of BMPR2, known as the principal mutation factor of heritable PAH, induces EndMT in vitro and in vivo [ 7 , 11 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…EndMT is a process whereby ECs lose their key endothelial traits and start expressing mesenchymal markers. As such, EndMT may directly or indirectly contribute to PAH, by EC transformation into smooth muscle-like cells with higher proliferative and migratory potential [10]. Accordingly, we recently underlined that various CFTR-impaired EC models showed limited EndMT, which might represent a secondary event due to CFTR-related endothelial dysfunction (figure 1).…”
mentioning
confidence: 99%
“…Histologically, PAH is characterised by the muscularisation of arterioles, intimal fibrosis and medial hypertrophy, and the hyperproliferation of ECs and vSMCs, as was found from CFTR-impaired models (figure 1) [2]. Multiple studies have also characterised endothelial-to-mesenchymal transition (EndMT) to be involved in the vascular remodelling in PAH [10]. EndMT is a process whereby ECs lose their key endothelial traits and start expressing mesenchymal markers.…”
mentioning
confidence: 99%